The Requirements of Academic Accounting Education in the light of the trends towards adopting International Financial Reporting Standards: A Field study in the universities of the Kurdistan Region - Iraq - Hassan, Enas; Abdullah, Sizar (Humanities Journal of University of Zakho, 2020)
This study evaluates the ability of accounting education in the universities of the Kurdistan Region-Iraq to identify the extent of its response to the requirements of the IFRS adoption decision. This study derives its importance from the importance of accounting education, as it represents the basic focus to raise the efficiency and quality of accounting education outputs, which in turn provides an opportunity for the universities of the region to identify weaknesses and extrapolate the current reality of accounting education and show the necessary requirements and areas that must be worked on to support IFRS adoption decision in the region. This study adopts the inductive method, where a questionnaire was prepared to collect the data, which was distributed to a group of academics in the region’s governmental and private universities. The results show that there is a positive and significant impact of the IFRS adoption decision on the accounting education requirements, which indicates that improving accounting education requires more attention to developing academic resources, teaching methods, as well as training and qualifying the teaching staff. This, in turn, results narrowing of the gap between the level of the actual performance of accounting education and the performance required to obtain outputs that meet the requirements and needs of the labor market, particularly in the modern business environment. This study suggests that there is a necessity of developing accounting education requirements in the region’s universities in general and governmental ones in particular, this may happen through the development of curricula, raising the efficiency of faculty members, in addition to updating teaching methods in the accounting departments in a way that achieves complementarity between these elements.